Character Education Values in the Javanese Gendhing “Pepeling” by Ki H. Anom Suroto: An Analysis of the Lyrics and Its Implications for Character Building among Elementary School Students - Pujiyana; Sawitri (CV Kalimasada Group, 2026)
This study analyzes the character education values embedded in the Javanese gendhing “Pepeling” composed by Ki H. Anom Suroto and examines its implications for character development among elementary school students. Although the gendhing is widely performed in Javanese religious and wayang gatherings, scholarly studies that examine its character education values for elementary education remain limited; this gap motivates the present study. The research employed a qualitative, descriptive-analytical approach using content analysis of the gendhing lyrics, supported by a literature review on character education and Javanese karawitan and complemented by hermeneutic interpretation of the Javanese linguistic symbols. The findings reveal four core character values: (1) spiritual awareness and commitment to worship, (2) consistency (istiqomah) and discipline, (3) patience and tawakal (trust in God), and (4) eling lan waspada (being mindful and cautious). These values correspond closely to the moral knowing, moral feeling, and moral action components of character formation and to the religious dimension of national character education. They are highly relevant for integration into elementary school character education through a local-wisdom-based approach. The study recommends that teachers use traditional Javanese gendhing as a contextual and meaningful medium for internalizing character values among elementary school students while contributing to cultural preservation